MENINGKATKAN MOTIVASI BELAJAR DENGAN PENDEKATAN CTL MODEL PEMBELAJARAN LANGSUNGKELAS XI SMAN 6 PONTIANAK - Susanti Susanti; Maria Ulfah; Achmadi Achmadi (Universitas Tanjungpura, 2020)
AbstractThis study aims to improve teacher performance in improving student learning motivation with the CTL approach to direct learning models in economic subjects. The research method used is the classroom action research (CAR) method with a qualitative and collaborative descriptive approach. The subjects in this study were students of class XI IPS 3 of SMA Negeri 6 Pontianak, totaling 31 students. Data collection techniques used are observation and documentation. The instruments used were observation sheets and cameras to take pictures in each cycle. The study was conducted in two cycles in which each cycle consisted of meetings I and II. The results of the acquisition data in the first cycle showed the learning motivation of meeting I was 40.2% and meeting II was 52.11%. Reflection was also carried out on the implementation of teaching the teacher to improve the results of the first cycle. The results of the second cycle showed students' motivation at meeting I was 64.3% and meeting II was 77%. From the data obtained, it can be concluded that after applying the CTL approach the direct learning model experienced positive changes, namely student motivation has increased and has reflected the achievement of all indicators of student motivation.Keywords: CTL Approach, Direct Learning Model, Learning Motivation